(untitled) (Development Service Industry Management, 2023)
Today, marketing research is one of the main functions of any company’s marketing activities. Marketing research provides top management with information for making management decisions. The more reliable, accurate and timely this information is, the more chances a company has to better meet the needs of consumers, outperform its competitors and thereby succeed in the market. Marketing as a business philosophy means orientation of all activities of the entire company − from design and production to sales of goods − to meet the needs of consumers. Therefore, marketing research within this philosophy finds the answer to two main questions for the market: what is the demand and what is the supply. A correct assessment of these two sides of the market allows an organisation to identify unmet demand and meet demand with supply. Therefore, marketing research is aimed at identifying the needs of specific consumers and generating profits for the company or achieving other strategic goals by studying and forecasting the market and the behaviour of its actors.